2017
DOI: 10.1007/s11239-017-1593-y
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane inhibition during concurrent therapy with low-dose aspirin and over-the-counter naproxen sodium

Abstract: NCT02229461.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This study was initiated with 117 healthy subjects, and the pharmacodynamic interaction between ASA 81 mg and naproxen 220 mg was investigated with the data of 80 subjects. After 10 days of treatment, varying degrees of pharmacodynamic interaction were reported 1891 .…”
Section: -When Should Chronic Anticoagulation Be Stopped In Patients ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This study was initiated with 117 healthy subjects, and the pharmacodynamic interaction between ASA 81 mg and naproxen 220 mg was investigated with the data of 80 subjects. After 10 days of treatment, varying degrees of pharmacodynamic interaction were reported 1891 .…”
Section: -When Should Chronic Anticoagulation Be Stopped In Patients ...mentioning
confidence: 99%
“…Capone et al, concluded that ASA should be administered before naproxen to minimize drug interactions 1873 . Gurbel et al, evaluated the co-administrating of 81 mg of ASA and 220 mg of naproxen and reported that when naproxen was used for more than a certain period of time, it could interact with ASA, and this interaction could be reduced by taking ASA at least 30 minutes before naproxen 1891 .…”
Section: -When Should Chronic Anticoagulation Be Stopped In Patients ...mentioning
confidence: 99%
“…Naproxen seems to exhibit a direct anti‐viral activity, as this NSAID suppresses viral replication and N‐oligomerization in VeroA6 in vitro cells 109 . Interestingly, the association of low doses acetyl‐salicylic acid (ASA) with naproxen leads to a significant reduction in the production of thromboxane B2, a direct metabolite of platelets' thromboxane A2 110 . Nimesulide is a powerful inhibitor of the BOAT1 subunit in SARS‐CoV2 receptor, namely, the plasma membrane transporter of aminoacids, known as SLC6A19, which is linked with ACE2 in a dimer and stabilizes the link with SARS‐CoV2 Spike protein: nimesulide, therefore, hampers viral entry into the cell 111 …”
Section: Nsaids As the First Choice Recommended Drugs In The Covid‐19...mentioning
confidence: 99%
“…Furthermore, naproxen may exhibit a lower cardiovascular risk relative to other NSAIDS due to its lower COX-2 selectivity, and has been shown not to affect blood pressure nor demonstrate any increased risk of cardiovascular events from short-term use [38]. Likewise, naproxen has not been associated with the same degree of interaction with aspirin as seen with ibuprofen and thus may be a preferred NSAID for patients on long term low-dose aspirin therapy [38][39]43]. While the incidence of adverse events is enough to mandate prescription status for certain doses and durations of NSAIDS, the OTC equivalent regimens have an improved safety profile such that physician supervision is only required in some instances.…”
Section: Safety Generalmentioning
confidence: 99%
“…Concurrent use of aspirin and naproxen would be expected to increase the risk of bleeding as a result of a pharmacodynamic interaction. While NSAIDS, including naproxen, have shown to interfere with the irreversible inhibition of platelet COX-1 by aspirin, the incidence of clinically significant bleeding with respect to this interaction with naproxen remains to be explored [38][39]44].…”
Section: Bleeding Risk In the Post-surgical Settingmentioning
confidence: 99%